The role of knowledge management and sharing in cooperatives practices toward National Economic Recovery in the COVID-19 pandemic era - Nur Khasanah; Jaka Sriyana; Andjar Prasetyo; Vita Nurdinawati; Agustinus Hartopo; Heri Wahyudianto; Dewi Gartika; Mochammad Fahlevi (Frontiers Media S.A., 2022)
The National Economic Recovery (NER) Program is one of the responses initiated by the government in Indonesia's economic recovery due to the impact of COVID-19, the target is to reduce the activities of affected communities, including cooperatives. One of the priority aspects for the program to run well and smoothly is the role of institutions in knowledge management and process sharing. This paper examines the role of knowledge management and sharing in cooperatives with qualitative limitations at the knowledge process level, knowledge design level, strategic interaction level, social participation level, academic and scientific ecosystem level, and network and partnership level. A qualitative description becomes a research method with secondary data in the form of a comparison of cooperatives in 2019-2021 as a representation before and during the COVID-19 pandemic. COVID-19 secondary data for 20 months from April 2020 to September 2022 in Indonesia dynamically also support sharpening the analysis. The source of cooperative data is from the publications of the Ministry of Cooperatives and SMEs, while the source of COVID-19 data comes from the publication of the COVID-19 Task Force. The analysis is carried out by building qualitative aspects into quantitative ones that can be formulated in the form of cooperative applications. The result is that the application of the knowledge process level, knowledge design level, strategic interaction level, social participation level, academic and scientific ecosystem level, and network and partnership level can improve decision-making, capture, share, and measure institutional knowledge for the success of the NER Program.